Resin composition, release film, adhesive sheet, and method for using adhesive sheet
Patent Information
- Application Number
- JP2023139348
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-08-29
- Publication Date
- 2025-03-13
AI Technical Summary
【0009】 本発明の離型フィルムによれば、粘着剤に対し超軽剥離性を実現しながらも、プレス処理により離型層の剥離特性が変化しにくい離型フィルム、該離型フィルムを用いた粘着シート(フィルム積層体)、及び該離型フィルムを形成するための樹脂組成物を提供することができる。
Smart Images

Figure 2025033563000005 
Figure 2025033563000001 
Figure 2025033563000002
Abstract
Description
[Technical field]
[0001] The present invention relates to a resin composition, a release film, an adhesive sheet, and a method for using the adhesive sheet. [Background technology]
[0002] Conventionally, release films using polyester film as a base material have been used for various purposes due to their excellent properties such as mechanical strength, dimensional stability, chemical resistance, and optical properties, and excellent cost performance. For example, they are used for various optical purposes such as polarizing plates for liquid crystal displays (hereinafter abbreviated as "LCD"), retardation plates, organic electroluminescence (hereinafter abbreviated as "organic EL") components, and various display components.
[0003] In recent years, the adhesive design of optically transparent adhesive sheets (OCA) / adhesive sheet components for organic electroluminescence (EL) has been progressing toward stronger adhesion, lower elasticity, and thinner thickness. Accordingly, silicone release films to protect adhesive sheets are required to have even lighter release properties than before. Methods for making a silicone release film easier to release include formulating the film so that the amount of functional groups remaining in the silicone layer after curing is reduced, or applying a thick silicone layer. On the other hand, when the silicone release film is made to have a light release property by the above-mentioned method, when the film is wound into a roll, the opposite side to the silicone layer sticks to the film, blocking occurs, and the silicone layer is damaged, causing heavy release, peeling electrification, deformation of the film, and non-uniform wettability of the adhesive. In particular, when a coating layer (in-line coating layer) such as an antistatic layer is formed on the opposite side, blocking tends to become even worse. Therefore, as a countermeasure against blocking, for example, a method of containing large particles (lubricant) in the base film or containing particles in the resin layer (coating layer) on the film has been used (see Patent Documents 1 to 3). [Prior art documents] [Patent documents]
[0004] [Patent Document 1] JP 2004-255704 A [Patent Document 2] JP 2017-61081 A [Patent Document 3] JP 2016-165825 A Summary of the Invention [Problem to be solved by the invention]
[0005] However, when large particles are contained in a base film, this can hinder foreign body inspection, cause scratches due to protrusions caused by the large particles, or cause particles to fall off and generate foreign bodies.
[0006] The present invention has been made in consideration of the above-mentioned circumstances, and the problem to be solved is to provide a release film which realizes ultra-easy peelability from adhesives while the peel properties of the release layer are not easily changed by press processing, an adhesive sheet (film laminate) using the release film, and a resin composition for forming the release film. [Means for solving the problem]
[0007] Means of Solving the Problems The present inventors have conducted intensive research in light of the above circumstances and have found that the above problems can be solved by using a resin composition having a specific structure, thereby completing the present invention. That is, the present invention provides the following [1] to
[19] .
[0008] [1] A resin composition comprising a curable silicone resin, a crosslinking agent A, and a catalyst, wherein the crosslinking agent A is a silicone crosslinking agent, and the proportion of SiH groups among the substituents bonded to the siloxane moieties is 25 mol % or more and 42 mol % or less. [2] The resin composition according to the above [1], comprising a crosslinker B in which the proportion of SiH groups among the substituents bonded to the siloxane moieties is greater than that of crosslinker A. [3] The resin composition according to the above [2], wherein the proportion of SiH groups among the substituents bonded to the siloxane moieties of the crosslinking agent B is 30 mol % or more and 50 mol % or less. [4] The resin composition according to any one of the above [1] to [3], wherein the curable silicone resin contains two or more crosslinkable reactive groups and has a number average molecular weight of 3,000 to 250,000. [5] The resin composition according to any one of the above [1] to [4], wherein the curable silicone resin has a branched structure in a main chain containing a siloxane bond. [6] The resin composition according to any one of the above [1] to [5], which is diluted with a solvent. [7] A release film comprising a resin layer on at least one surface of a base film, the resin layer being a cured product of the resin composition according to any one of the above [1] to [6]. [8] The release film according to the above [7], further comprising an undercoat layer between the base film and the resin layer. [9] The release film according to the above [8], wherein the undercoat layer is an antistatic layer.
[10] The release film according to the above [9], wherein the undercoat layer contains at least one of the following compounds (a) to (c): (a) at least one selected from the group consisting of a polymer in which a compound made of thiophene or a thiophene derivative is doped with another anionic compound, a self-doped polymer having an anionic group in a compound made of thiophene or a thiophene derivative, and a polymer containing, as a component, a monomer having an alkylsulfonate ion as a counter ion; (b) Polyhydroxy compounds (c) one or more compounds selected from the group consisting of polyurethane resins, polyester resins, and acrylic resins
[11] At least one surface has a surface resistivity of 1×10 12 The release film according to the above [9] or
[10] , having a resistivity of Ω / □ or less.
[12] The release film according to the above [8], wherein the undercoat layer is an oligomer sealing layer.
[13] The release film according to any one of the above [7] to
[12] , wherein the base film is a polyester film.
[14] The release film according to the above
[13] , wherein the polyester film has a three-layer structure.
[15] A pressure-sensitive adhesive sheet comprising the release film according to any one of the above [7] to
[14] and, via an adhesive layer, another release film.
[16] The pressure-sensitive adhesive sheet according to
[15] above, wherein the pressure-sensitive adhesive layer is formed from an acrylic pressure-sensitive adhesive layer composition.
[17] The adhesive sheet according to
[15] or
[16] above, which is for use as an optically transparent adhesive sheet.
[18] A method for using the pressure-sensitive adhesive sheet according to any one of the above
[15] to
[17] , comprising peeling off the other release film and then attaching the exposed surface of the pressure-sensitive adhesive layer to an optical member.
[19] A method for using the adhesive sheet described in
[18] above, wherein the optical component is a polarizing plate or a touch sensor. Effect of the Invention
[0009] According to the release film of the present invention, it is possible to provide a release film which realizes ultra-light peelability from adhesives while the peel properties of the release layer are not easily changed by press processing, an adhesive sheet (film laminate) using the release film, and a resin composition for forming the release film. [Brief description of the drawings]
[0010] [Figure 1] FIG. 1 is a schematic diagram showing a release film of the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0011] An example of an embodiment of the present invention will be described in detail below. However, the present invention is not limited to the embodiment described below, and can be modified and implemented as desired within the scope of the present invention. In this specification, when "X to Y" (X and Y are any numbers) is expressed, unless otherwise specified, it includes the meaning of "X or more and Y or less", as well as "preferably greater than X" or "preferably smaller than Y". In addition, when "X or more" (X is any number) or "Y or less" (Y is any number), it also includes the meaning of "preferably greater than X" or "preferably less than Y". In the following description, "film" and "sheet" are not clearly distinguished from each other, and when "film" is referred to, it includes "sheet", and when "sheet" is referred to, it includes "film".
[0012] [Resin composition] The resin composition of the present invention (hereinafter sometimes referred to as "the resin composition") comprises a curable silicone resin, a crosslinking agent A, and a catalyst, wherein the crosslinking agent A is a silicone crosslinking agent, and the proportion of SiH groups among the substituents bonded to the siloxane moieties is 25 mol % or more and 42 mol % or less.
[0013] <Curable silicone resin> The resin composition preferably contains a curable silicone resin as a main component resin. The main component resin means the resin having the largest mass ratio among the resins constituting the resin composition, and is assumed to account for 50 mass% or more, 75 mass% or more, 90 mass% or more, or 100 mass% of the resins constituting the resin composition.
[0014] The type of curable silicone resin may be any of the existing curing reaction types, such as heat curing types such as addition type and condensation type, and electron beam curing types such as ultraviolet curing type. A plurality of types of curable silicone resins may be used in combination. The type of curable silicone resin used in this embodiment is preferably an addition type heat curable silicone resin, since it does not produce by-products of the curing reaction and the physical properties of the cured film are stable. The form of the resin composition described below is not particularly limited, and may be any of a form dissolved in an organic solvent (solvent type), a solventless form (solventless type), and an aqueous emulsion form.
[0015] Solventless curable silicone is a silicone with a viscosity that can be applied without diluting with a solvent, and is a silicone resin with a relatively low molecular weight, consisting of a short polysiloxane chain.On the other hand, solvent-type curable silicone is a silicone resin with a high viscosity that cannot be applied without diluting with a solvent, and is a silicone with a relatively high molecular weight compared with solventless curable silicone.The curable silicone resin used in this embodiment may be either solvent-type or solventless type, but it is particularly preferable to use a resin composition diluted with a solvent from the viewpoint of uniform coat appearance without coat unevenness, and easy adjustment of the thickness of the resin layer, which is advantageous for thin film coating.
[0016] The curable silicone resin used in this embodiment preferably has a branched structure in the main chain containing a siloxane bond. When the main chain containing a siloxane bond has a branched structure, light releasability is easily obtained. In addition, as the curable silicone resin used in this embodiment, it is preferable to use a curable silicone resin containing a crosslinkable reactive group that has excellent light release properties from the viewpoint of release properties. The curable silicone resin containing a crosslinkable reactive group is preferably a diorganopolysiloxane having at least two, preferably three or more crosslinkable reactive groups bonded to silicon atoms in one molecule. As the curable silicone resin containing a crosslinkable reactive group, for example, one represented by the following formula (1) can be mentioned. R (3-a) Xa SiO-(RXSiO) m -(R2SiO) n -SiX a R (3-a) (1)
[0017] In formula (1), R is a monovalent hydrocarbon group having 1 to 10 carbon atoms, and X is an organic group containing a crosslinkable reactive group, and is particularly preferably an alkenyl group. a is an integer of 0 to 3, preferably 1, and m is 0 or more, but when a=0, m is 2 or more, and m and n are numbers that satisfy 100≦m+n≦20000, and the above formula (1) does not mean a block copolymer.
[0018] R is a monovalent hydrocarbon group having 1 to 10 carbon atoms. Specific examples include alkyl groups such as methyl, ethyl, propyl, and butyl; cycloalkyl groups such as cyclohexyl; and aryl groups such as phenyl and tolyl. Of these, methyl and phenyl groups are particularly preferred. X is an organic group containing a crosslinkable reactive group, preferably an organic group containing an alkenyl group, more preferably an alkenyl group, and even more preferably an alkenyl group having 2 to 10 carbon atoms. Specific examples of X include a vinyl group, an allyl group, a hexenyl group, an octenyl group, an acryloylpropyl group, an acryloylmethyl group, a methacryloylpropyl group, a cyclohexenylethyl group, and a vinyloxypropyl group, with a vinyl group or a hexenyl group being particularly preferred, and a vinyl group being particularly preferred. Specific examples include a dimethylsiloxane-methylhexenylsiloxane copolymer capped at both molecular chain terminals with trimethylsiloxy groups (96 mol% dimethylsiloxane units, 4 mol% methylhexenylsiloxane units), a dimethylsiloxane-methylhexenylsiloxane copolymer capped at both molecular chain terminals with dimethylvinylsiloxy groups (97 mol% dimethylsiloxane units, 3 mol% methylhexenylsiloxane units), and a dimethylsiloxane-methylhexenylsiloxane copolymer capped at both molecular chain terminals with dimethylhexenylsiloxy groups (95 mol% dimethylsiloxane units, 5 mol% methylhexenylsiloxane units).
[0019] The curable silicone resin used in this embodiment may have both functional groups of crosslinkable reactive groups such as alkenyl groups bonded to silicon atoms and hydrogen atoms (SiH groups) bonded to silicon atoms in one molecule, or may use silicone resins having each functional group separately, specifically silicone resins having crosslinkable reactive groups such as alkenyl groups bonded to silicon atoms in one molecule and silicone resins having hydrogen atoms (SiH groups) bonded to silicon atoms in one molecule in combination. Below, the crosslinkable reactive groups such as alkenyl groups are explained using alkenyl groups as a representative example.
[0020] In the substituents bonded to all siloxanes in the polysiloxane chain of the curable silicone resin used in this embodiment, the amount of alkenyl groups bonded to the polysiloxane chain is preferably 2.9 mol% or less, more preferably 2.8 mol% or less, even more preferably 2.7 mol% or less, and particularly preferably 2.6 mol% or less.The lower limit of the amount of alkenyl groups bonded to the polysiloxane chain relative to the amount of all siloxane components in the polysiloxane chain is not particularly limited, but is preferably 0.4 mol% or more, and more preferably 0.5 mol% or more. By setting the amount of alkenyl groups linked to the polysiloxane chain relative to the total amount of siloxane components in the polysiloxane chain within the above range, the resin layer contains a certain amount or more of alkenyl groups linked to the polysiloxane chain, so that the resin layer is sufficiently cured, and as a result, it is possible to suppress the transfer of silicone from the resin layer to the object to be adhered.On the other hand, by setting the amount of alkenyl groups linked to the polysiloxane chain relative to the total amount of siloxane components in the polysiloxane chain within the above range, the resin layer does not have an excessive amount of unreacted alkenyl groups, so that it is possible to prevent the peeling force from becoming heavy after exposure to air.
[0021] In this specification, the total amount of siloxane components in the polysiloxane chain of the curable silicone resin is calculated from the amount of functional groups such as alkenyl groups and Si-H groups linked to the side chains of the polysiloxane chain, and the amount of these functional groups (alkenyl group amount, SiH group amount, etc.) is 1 It can be calculated by H-NMR measurement. 1 H-NMR measurements are performed using CDCl3 as a solvent, with the peak derived from the methyl group of dimethylsiloxane as the chemical shift standard at a temperature of 30° C. The respective contents (mol%) of alkenyl groups and SiH groups relative to the total amount of siloxane components in the polysiloxane chain are calculated from the integral ratio of each functional group when the methyl group is used as the standard.
[0022] The number average molecular weight (Mn) of the curable silicone resin is preferably 2000 to 1,000,000, more preferably 3,000 to 250,000, and even more preferably 5,000 to 50,000. By setting the number average molecular weight (Mn) of the curable silicone resin within the above range, when an adhesive layer is laminated as an adhesion target, it is possible to prevent the low molecular weight silicone resin from eluting into the adhesive layer, and it is possible to suppress silicone migration. In addition, by setting the number average molecular weight (Mn) of the curable silicone resin within the above range, the resin composition can be brought into a viscosity range suitable for coating, and the fluidity of the resin composition can be prevented from decreasing, and streaky coating unevenness can be prevented from occurring, etc. This makes it possible to obtain a good surface state with high visibility and to easily smooth the surface of the resin layer. As described above, it is particularly preferable that the curable silicone resin in the present invention contains two or more crosslinkable reactive groups and has a number average molecular weight of 3,000 to 250,000.
[0023] From the same viewpoint as for the number average molecular weight, the mass average molecular weight (Mw) of the curable silicone resin is preferably 3,000 to 2,000,000, more preferably 5,000 to 500,000, and even more preferably 10,000 to 100,000.
[0024] The ratio (Mw / Mn) of the mass average molecular weight (Mw) to the number average molecular weight (Mn) of the curable silicone resin is preferably in the range of 1.0 to 5.0, more preferably 1.2 to 4.0, and even more preferably 1.5 to 3.5. By satisfying this range, the crosslinking reaction can be efficiently promoted and the distribution ratio of low molecular weight silicone resin can be reduced, so that the amount of unreacted components and low molecular weight components contained in the resin layer can be reduced, and low migration can be achieved. Furthermore, it is particularly preferable that the curable silicone resin has a branched structure in the main chain containing a siloxane bond, since this makes it easier to obtain light releasability. The resin composition of the present invention contains crosslinking agent A, which is a silicone crosslinking agent, and optionally contains crosslinking agent B. It is preferable that the mass average molecular weight (Mn), number average molecular weight (Mw), and Mw / Mn of the curable silicone resin (silicone base) excluding silicone crosslinking agents A and B are within the above-mentioned ranges.
[0025] <Crosslinking agent A> The resin composition of the present invention contains a crosslinking agent A. The crosslinking agent A is a silicone crosslinking agent, contains a polyorganosiloxane containing a SiH group, and the ratio of the SiH group to the substituents bonded to the siloxane moiety is 25 mol% or more and 42 mol% or less. The ratio of the SiH group is preferably 25 mol% or more and 38 mol% or less, more preferably 31 mol% or more and 38 mol% or less. Crosslinking agent A has the function of reacting with the curable silicone resin containing an alkenyl group to form a stronger silicone resin layer. As the polyorganosiloxane in the crosslinking agent A, it is preferable to use an organohydrogenpolysiloxane having at least two, preferably three or more, hydrogen atoms bonded to silicon atoms in one molecule. As the polyorganosiloxane, linear, branched, cyclic, etc. can be used, and examples thereof include compounds represented by the following formula (2), but are not limited to these. H b R 1 (3-b) SiO-(HR 1 SiO)x -(R 1 2SiO) y -SiR 1 (3-b) H b (2)
[0026] In formula (2), R 1 is a monovalent hydrocarbon group having 1 to 6 carbon atoms and not containing an aliphatic unsaturated bond. b is an integer from 0 to 3, and x and y are each an integer. Specific examples include methylhydrogenpolysiloxane capped with trimethylsiloxy groups at both molecular chain terminals, dimethylsiloxane-methylhydrogensiloxane copolymer capped with trimethylsiloxy groups at both molecular chain terminals, methylhydrogenpolysiloxane capped with dimethylhydrogensiloxy groups at both molecular chain terminals, and dimethylsiloxane-methylhydrogensiloxane copolymer capped with dimethylhydrogensiloxy groups at both molecular chain terminals.
[0027] <Crosslinking agent B> The resin composition of the present invention can contain, in addition to crosslinking agent A, crosslinking agent B, which is a silicone crosslinking agent in which the proportion of SiH groups among the substituents bonded to the siloxane moieties is higher than that of crosslinking agent A. By including crosslinking agent B, the curability and adhesion of the resin layer formed by the resin composition of the present invention are further improved. For the crosslinker B, the proportion of SiH groups among the substituents bonded to the siloxane moieties is preferably 30 mol % or more and 50 mol % or less, more preferably 31 mol % or more and 50 mol % or less, and particularly preferably 35 mol % or more and 50 mol % or less. By setting the proportion of SiH groups among the substituents bonded to the siloxane moieties within the above range, the dispersibility of the crosslinking agent in the resin film is improved while maintaining sufficient curability, and an excessive amount of unreacted SiH groups is not present in the resin layer, preventing the peel force from increasing after heating.
[0028] In the present embodiment, it is preferable to use a mixture of crosslinking agent A and crosslinking agent B. By using a mixture of them, it is possible to obtain the effects of both the excellent curing property of crosslinking agent A and the excellent adhesion to the base of crosslinking agent B. The mixing ratio of crosslinking agent A to crosslinking agent B is not particularly limited, but is preferably in the range of 1:99 to 99:1, more preferably in the range of 10:90 to 90:10, and particularly preferably in the range of 15:85 to 85:15. Furthermore, the types of crosslinking agents to be mixed are not limited to two, but three or more types may be mixed.
[0029] In this embodiment, the molar ratio of the amount of SiH groups contained in the resin composition to the amount of alkenyl groups linked to the polysiloxane chain of the curable silicone resin (SiH groups / alkenyl groups) is preferably 3.5 or less, more preferably 3.0 or less, and even more preferably 2.5 or less. The lower limit of the SiH groups / alkenyl groups is not particularly limited, but is preferably 1.0 or more, and more preferably 1.2 or more, for example. The content of the SiH group may be the amount of the SiH group contained in the resin composition, but it is preferable that the amount of the SiH group is the amount of the SiH group consisting of hydrogen atoms bonded to silicon atoms of the polysiloxane chain of the curable silicone resin. 1 It can be calculated by H-NMR measurement.
[0030] The content of the crosslinking agent in the resin composition is preferably in the range of 0.1 to 10.0 parts by mass, more preferably 0.5 to 8.0 parts by mass, and even more preferably 1.0 to 5.0 parts by mass, per 100 parts by mass of the curable silicone resin. When the amount is equal to or greater than the lower limit, the effect of the crosslinking agent can be sufficiently obtained, and when the amount is equal to or less than the upper limit, a sufficiently light peeling property can be obtained.
[0031] A curing catalyst for promoting an addition reaction may be added to the resin composition. As the curing catalyst, a platinum-based catalyst is preferably added. Examples of platinum-based catalysts include platinum-based compounds such as chloroplatinic acid, an alcohol solution of chloroplatinic acid, a complex of chloroplatinic acid and an olefin, and a complex of chloroplatinic acid and an alkenylsiloxane, platinum black, platinum-supported silica, and platinum-supported activated carbon. The content of the curing catalyst in the resin composition is preferably 0.5 to 500 ppm by mass, more preferably 5 ppm by mass or more, and even more preferably 10 ppm by mass or more, in terms of metal, relative to the curable silicone resin. The content of the curing catalyst is preferably 300 ppm by mass or less, and even more preferably 200 ppm by mass or less. When the platinum catalyst content in the resin composition is equal to or more than the lower limit, the curing reaction proceeds sufficiently, so that sufficient peeling force is obtained when the resin layer is formed, and there is no problem such as deterioration of the coat surface condition. On the other hand, when the platinum catalyst content in the resin composition is equal to or less than the upper limit, in addition to being advantageous in terms of cost, it is possible to suppress the occurrence of process problems such as increased reactivity and generation of gel foreign matter.
[0032] Since the curable silicone resin is very reactive, acetylene alcohol may be added as a reaction inhibitor in some cases. The component is an organic compound having a carbon-carbon triple bond and a hydroxyl group, preferably a compound selected from the group consisting of 3-methyl-1-butyn-3-ol, 3,5-dimethyl-1-hexyn-3-ol and phenylbutynol. The content of the reaction inhibitor is preferably 0.001 to 5.0 parts by mass, more preferably 0.01 to 2.0 parts by mass, even more preferably 0.05 to 1.5 parts by mass, and most preferably 0.1 to 0.5 parts by mass, per 100 parts by mass of the total amount of the resin composition (based on non-volatile components). By setting the content of the reaction inhibitor within the above range, the curable silicone resin is not inhibited from curing without decreasing the reaction activity, and the easy peelability of the resin layer can be ensured.
[0033] In the present resin composition, a catalyst other than a platinum catalyst may be used in combination for the purpose of promoting hydrolysis and condensation reactions. Specific examples of such catalysts include organic acids such as acetic acid, butyric acid, maleic acid, and citric acid, inorganic acids such as hydrochloric acid, nitric acid, phosphoric acid, and sulfuric acid, basic compounds such as triethylamine, organic metal salts such as tetrabutyl titanate, dibutyltin dilaurate, dibutyltin diacetate, dibutyltin dioctate, dibutyltin diolate, diphenyltin diacetate, dibutyltin oxide, dibutyltin dimethoxide, dibutylbis(triethoxysiloxy)tin, and dibutyltin benzyl maleate, and fluorine-containing compounds such as KF and NHF. The above catalysts may be used alone or in combination of two or more. Among them, organic metal salts are preferable in that they provide good coating film durability.
[0034] The resin composition may also contain a light release agent. Examples of light release agents include low molecular weight siloxane compounds having no alkenyl groups and a mass average molecular weight (Mw) of less than 10,000, and specific examples include hexamethylcyclotrisiloxane, octamethylcyclotetrasiloxane, and decamethylcyclopentasiloxane. Examples of other compounds of these low molecular weight cyclic siloxanes include dimethylsiloxane oligomers blocked at both ends of the molecular chain with trimethylsiloxy groups; dimethylsiloxane oligomers blocked at both ends of the molecular chain with dimethylhydroxysiloxy groups, but are not limited thereto. The content of the light release agent in the present resin composition is, for example, 15% by mass or less, preferably 10% by mass or less, and more preferably 5% by mass or less, based on the non-volatile components.
[0035] The resin composition can be diluted with a solvent as necessary. Examples of dilution solvents include aromatic hydrocarbons such as toluene, aliphatic hydrocarbons such as hexane, heptane, and isooctane, esters such as ethyl acetate and butyl acetate, ketones such as methyl ethyl ketone (MEK) and isobutyl methyl ketone, alcohols such as ethanol and 2-propanol, and ethers such as diisopropyl ether and dibutyl ether. These are preferably used alone or in combination, taking into consideration solubility, coatability, boiling point, and the like.
[0036] The resin composition may also contain an organosilicon compound represented by the following formula (3) in order to improve the coating adhesion to a substrate film, which will be described later. Si(X) d (Y) e (R 1 ) f (3) In the above formula (3), X is an organic group having at least one selected from an epoxy group, a mercapto group, a (meth)acryloyl group, an alkenyl group, a haloalkyl group, and an amino group; R 1 is a monovalent hydrocarbon group having 1 to 10 carbon atoms, Y is a hydrolyzable group, d is an integer of 1 or 2, e is an integer of 2 or 3, f is an integer of 0 or 1, and d+e+f=4.
[0037] The organosilicon compound represented by formula (3) can be one having two or three hydrolyzable groups Y capable of forming a siloxane bond by hydrolysis and condensation reaction. In formula (3), the monovalent hydrocarbon group R 1 The number of carbon atoms is preferably 1 to 10, and a methyl group, an ethyl group, or a propyl group is particularly preferable.
[0038] In formula (3), examples of the hydrolyzable group Y include the following: methoxy group, ethoxy group, butoxy group, isopropenoxy group, acetoxy group, butanoxime group, and amino group. These hydrolyzable groups may be used alone or in combination. The use of a methoxy group or an ethoxy group is particularly preferred because it can provide the coating material with good storage stability and has suitable hydrolyzability.
[0039] Specific examples of the organosilicon compound contained in the resin composition include vinyltrimethoxysilane, γ-glycidoxypropyltrimethoxysilane, γ-glycidoxypropylmethyldiethoxysilane, β-(3,4-epoxycyclohexyl)ethyltrimethoxysilane, γ-mercaptopropyltrimethoxysilane, γ-methacryloxypropyltrimethoxysilane, γ-acryloxypropyltrimethoxysilane, γ-aminopropyltriethoxysilane, 5-hexenyltrimethoxysilane, p-styryltrimethoxysilane, trifluoropropyltrimethoxysilane, γ-glycidoxypropyltriethoxysilane, and γ-glycidoxypropylmethyldiisopropenoxysilane.
[0040] It is preferable that the resin composition does not substantially contain particles. By substantially not containing particles in the resin composition, a uniform resin layer can be formed, and therefore, peel stability can be achieved, and when an adhesive layer is laminated as an attachment target, there is no risk of contamination due to particle drop-off, and low migration can be achieved. Note that, "substantially not containing" means that the resin composition may contain particles as long as the amount is small enough not to inhibit the effects of the present invention, and for example, particles that are inevitably mixed in may be included. The specific content of particles in the resin composition is, for example, less than 0.05% by mass, preferably less than 0.01% by mass, and more preferably less than 0.0001% by mass, based on non-volatile components.
[0041] Furthermore, within the scope of the present invention, the resin composition may contain, as necessary, an antifoaming agent, a coatability improving agent, a thickener, an organic lubricant, an antistatic agent, a conductive agent, an ultraviolet absorber, an antioxidant, a foaming agent, a dye, a pigment, etc.
[0042] [Release film] The present embodiment relates to a release film (hereinafter also referred to as "the present release film") in which a resin layer formed by curing a resin composition is laminated on at least one surface of a base film. Here, the resin composition is the above-mentioned resin composition of the present invention. The present release film may have a resin layer on at least one side of the base film, and may have resin layers on both sides.
[0043] Since the present release film has the above-mentioned structure, it has extremely excellent easy releasability and release stability. That is, the present release film has both easy releasability and release stability, and when the coating liquid is aged for 8 hours, applied to the base film, cured, and a resin layer is formed, the easy releasability is maintained without becoming heavy releasable by the press treatment.
[0044] In this way, the present release film combines easy peelability and peel stability, and is suitable for applications in which changes in the peelability of the release layer and deterioration of the appearance of the resin layer surface are undesirable. For example, the release film is suitable for use in various applications in which bonding is performed via an adhesive layer, such as in the manufacture of capacitive touch panels, for example, optical components used in LCDs (polarizing plates, retardation plates, prism sheets, conductive films, resin films, glass substrates, etc.) and organic electroluminescence components, for the manufacture of various display components such as LCDs, as well as for protecting various adhesive layers. The release film with an adhesive layer may be a film laminate in which an optical member is attached to the surface of the adhesive layer. Such a film laminate can be produced by peeling off the release film and attaching the optical member to an adherend by the exposed adhesive layer. Examples of the optical member include a polarizing plate and a touch sensor. The optical member may also be an in-vehicle optical member such as a touch panel mounted on an automobile.
[0045] <Base film> The material of the base film in the present release film is not particularly limited as long as it has a film shape. For example, the base film may be made of paper, resin, metal, etc. Among these, from the viewpoint of mechanical strength and flexibility, the base film is preferably made of resin.
[0046] Examples of the resin substrate film include films formed from polymers such as polyethylene, polypropylene, polyester, polystyrene, polycarbonate, polyethersulfone, polyamide, polyimide, etc. Furthermore, as long as they can be formed into a film, they may be mixtures of these materials (polymer blends) or composites of their constituent units (copolymers). Among the above-listed films, it is particularly preferable that the base film is a polyester film, since it has excellent physical properties such as heat resistance, flatness, optical properties, and strength.
[0047] (Polyester film) The polyester film constituting the above-mentioned base film may be a single layer structure or a multi-layer structure. When the polyester film has a multi-layer structure, it may have a multi-layer structure of four or more layers in addition to a two-layer or three-layer structure, as long as it does not exceed the gist of the present invention, and is not particularly limited. Among them, it is preferable that the base film is a polyester film having at least a three-layer structure. Moreover, as the polyester film, a biaxially oriented polyester film is preferable from the viewpoints of thinning and dimensional stability.
[0048] The polyester film contains polyester as a main component resin. In this specification, the main component resin means a resin having the largest mass ratio among the resins constituting the polyester film, and may be 50 mass % or more, 75 mass % or more, 90 mass % or more, or may be 100 mass % of the resins constituting the polyester film.
[0049] The polyester used for the base film of the release film may be either a homopolyester or a copolymer polyester. In the case of a homopolyester, it is preferable to use one obtained by polycondensation of an aromatic dicarboxylic acid and an aliphatic glycol. Examples of the aromatic dicarboxylic acid include terephthalic acid and 2,6-naphthalenedicarboxylic acid, and examples of the aliphatic glycol include ethylene glycol, diethylene glycol, and 1,4-cyclohexanedimethanol. A representative polyester is polyethylene terephthalate.
[0050] When the base film contains a copolymerized polyester, the copolymerized polyester may be one obtained by polycondensation of a dicarboxylic acid component and a glycol component. The dicarboxylic acid component may be one or more of isophthalic acid, phthalic acid, terephthalic acid, 2,6-naphthalenedicarboxylic acid, adipic acid, sebacic acid, oxycarboxylic acid (e.g., p-oxybenzoic acid, etc.), and the glycol component may be one or more of ethylene glycol, diethylene glycol, propylene glycol, butanediol, 4-cyclohexanedimethanol, neopentyl glycol, etc. The copolymerized polyester may contain a third component in addition to the dicarboxylic acid component and the glycol component, but the content of the third component is preferably 30 mol% or less based on the total of the carboxylic acid component and the glycol component.
[0051] The intrinsic viscosity (IV) of the polyester is preferably 0.5 dL / g or more, more preferably 0.52 dL / g or more, and even more preferably 0.54 dL / g or more. The intrinsic viscosity (IV) of the polyester is, for example, preferably 1 dL / g or less, and more preferably 0.8 dL / g or less. By setting the intrinsic viscosity of the polyester within the above range, the production efficiency of the polyester film can be more effectively improved.
[0052] The polymerization catalyst used in polycondensing the polyester is not particularly limited, and can be a conventionally known compound. Examples of the polymerization catalyst include antimony compounds, titanium compounds, germanium compounds, manganese compounds, aluminum compounds, magnesium compounds, and calcium compounds. Among these, it is preferable to use titanium compounds or germanium compounds because they have high catalytic activity, can be polymerized in small amounts, and have a small amount of metal remaining in the film, resulting in high film brightness. In addition, it is more preferable to use titanium compounds because germanium compounds are expensive.
[0053] When a titanium compound is used as a polymerization catalyst, the titanium element content in the polyester is preferably 50 ppm or less, more preferably 1 to 20 ppm, and even more preferably 2 to 10 ppm. By making the titanium compound content equal to or less than the upper limit, the polyester can be prevented from being deteriorated during the melt extrusion process of the polyester, and a film with reduced yellowing can be easily obtained. In addition, by making the titanium compound content equal to or more than the lower limit, the polymerization efficiency of the polyester can be increased, and a film with sufficient strength can be easily obtained.
[0054] In addition, when a titanium compound is used as a polymerization catalyst, it is preferable to use a phosphorus compound to reduce the activity of the titanium compound in order to suppress deterioration during the melt extrusion process. As the phosphorus compound, orthophosphoric acid is preferable in consideration of the productivity and thermal stability of the polyester. The phosphorus element content is preferably in the range of 1 to 300 mass ppm, more preferably 3 to 200 mass ppm, and even more preferably 5 to 100 mass ppm relative to the amount of polyester to be melt extruded. By setting the content of the phosphorus compound to the above upper limit value or less, it is possible to suppress gelation and foreign matter, and by setting the content of the phosphorus compound to the above lower limit value or more, it is possible to sufficiently reduce the activity of the titanium compound, making it easier to obtain a film with suppressed yellowing.
[0055] In order to suppress the amount of precipitation of oligomer components, the polyester film may be produced using a polyester having a low content of oligomer components as a raw material. As a method for producing a polyester having a low content of oligomer components, various known methods can be used, such as a method of performing solid-phase polymerization after the production of a polyester.
[0056] The amount of oligomer components precipitated may be suppressed by forming the polyester film into a three-layer or more layer and forming the outermost layer of the polyester film from a polyester raw material having a low content of oligomer components. The polyester may be obtained by melt polycondensation under reduced pressure at a higher reaction temperature after esterification or transesterification.
[0057] The polyester film may contain a biomass-derived polyester. For example, when the polyester film has a multi-layer structure, it may have a layer containing a biomass-derived polyester as a main component and a layer containing a fossil fuel-derived polyester as a main component.
[0058] The polyester film may contain recycled materials, such as edges of polyester films that were not used in the polyester film production line, recycled polyesters derived from PET bottles, and recycled polyesters derived from packaging materials.
[0059] It is also possible to incorporate an ultraviolet absorbing agent into the polyester film in order to improve the weather resistance of the film and prevent deterioration of the adherend (e.g., liquid crystal), etc. The ultraviolet absorbing agent is a compound that absorbs ultraviolet light and is not particularly limited as long as it can withstand the heat applied during the manufacturing process of the polyester film.
[0060] As the ultraviolet absorbing agent, there are organic ultraviolet absorbing agents and inorganic ultraviolet absorbing agents, and from the viewpoint of transparency, organic ultraviolet absorbing agents are preferred.As the organic ultraviolet absorbing agent, there are no particular limitations, but for example, cyclic imino esters, benzotriazoles, benzophenones, etc. are mentioned.From the viewpoint of durability, cyclic imino esters and benzotriazoles are more preferred.In addition, it is also possible to use two or more kinds of ultraviolet absorbing agents in combination.
[0061] It is also possible to blend particles into the polyester film for the main purpose of imparting easy slippage and preventing scratches in each process. When blending particles, the type of particles to be blended is not particularly limited as long as it is a particle that can impart easy slippage, and specific examples include inorganic particles such as silica, calcium carbonate, magnesium carbonate, barium carbonate, calcium sulfate, calcium phosphate, magnesium phosphate, kaolin, aluminum oxide, zirconium oxide, and titanium oxide, and organic particles such as acrylic resin, styrene resin, urea resin, phenol resin, epoxy resin, and benzoguanamine resin. Furthermore, precipitated particles obtained by precipitating and finely dispersing a part of a metal compound such as a catalyst during the polyester production process can also be used. Among these, silica particles and calcium carbonate particles are particularly preferred because they are easy to be effective even in small amounts.
[0062] The average particle size of the particles is preferably in the range of 0.01 to 5 μm, more preferably 0.03 to 4 μm, and further preferably 0.05 to 3.5 μm. When the average particle size of the particles is equal to or less than the upper limit, the haze of the film is kept low and the film has slip properties.
[0063] The particle content in the polyester film is preferably 5% by mass or less, more preferably in the range of 0.001 to 3% by mass, further preferably 0.01 to 1% by mass, and particularly preferably 0.05 to 1% by mass. By keeping the particle content within the above range, it is possible to prevent the lubricity from decreasing while increasing the transparency of the film.
[0064] The shape of the particles to be used is not particularly limited, and any of spherical, blocky, rod-like, flat, etc. can be used, and there is no particular limit to the hardness, specific gravity, color, etc. Two or more types of these particles may be used in combination as necessary.
[0065] The method of adding particles to the polyester layer is not particularly limited, and any conventionally known method can be used. For example, the particles can be added at any stage in the production of the polyester constituting each layer, but it is preferable to add the particles after the completion of the esterification or transesterification reaction.
[0066] In addition to the above-mentioned particles, the polyester film of the present invention may contain, if necessary, antioxidants, antistatic agents, heat stabilizers, lubricants, dyes, pigments, etc.
[0067] The thickness of the polyester film is not particularly limited as long as it is within a range that allows film formation, but is preferably 10 to 300 μm, more preferably 15 to 200 μm, even more preferably 25 to 125 μm, and most preferably 38 to 75 μm. When the polyester film has a multi-layer structure, the total thickness of all layers is preferably within the above range.
[0068] (Production method of polyester film) Next, a manufacturing example of a polyester film will be specifically described, but the manufacturing example is not limited to the following manufacturing example. For example, when a biaxially oriented polyester film is manufactured, the polyester raw material described above is first melt-extruded from a die using an extruder, and the molten sheet is cooled and solidified by a cooling roll to obtain an unstretched sheet. When the polyester film has a multilayer structure, the polyester raw material constituting each layer is supplied to each extruder, melted, co-extruded, and cooled and solidified. Here, the cooling is preferably performed to a temperature below the glass transition point of the polymer, for example, to obtain an unoriented sheet (unstretched sheet) in a substantially amorphous state. In addition, in order to improve the flatness of the sheet, it is preferable to increase the adhesion between the sheet and the rotating cooling drum, and an electrostatic application adhesion method or a liquid application adhesion method is preferably adopted. The raw polyester may be supplied to the extruder after being appropriately dried as pellets or the like. In addition, particles, ultraviolet absorbers, other additives, etc. may be appropriately blended into the pellets.
[0069] Next, the unstretched sheet is stretched in one direction by a roll or tenter type stretching machine. The stretching temperature is usually 70 to 120°C, preferably 80 to 110°C, and the stretching ratio is usually 2.5 to 7 times, preferably 3.0 to 6 times. Next, the sheet is stretched in a direction perpendicular to the first-stage stretching direction at usually 70 to 170°C and at a stretching ratio of usually 2.5 to 7 times, preferably 3.0 to 6 times. The sheet is then heat-treated under tension or relaxation of 30% or less at a temperature of 180 to 270°C to obtain a biaxially oriented film. In the above stretching, a method of stretching in one direction in two or more stages can also be adopted. In that case, it is preferable to perform the stretching so that the final stretching ratios in both directions are each within the above range.
[0070] In addition, simultaneous biaxial stretching can also be used for the production of polyester films. The simultaneous biaxial stretching method is a method in which an unstretched sheet is simultaneously stretched and oriented in the machine direction and the width direction under a temperature controlled condition usually at 70 to 120°C, preferably 80 to 110°C, and the stretching ratio is usually 4 to 50 times, preferably 7 to 35 times, more preferably 10 to 25 times in terms of area ratio. Then, the sheet is subsequently heat-treated under tension or relaxation of 30% or less at a temperature of 170 to 270°C to obtain a stretch-oriented film. As for the simultaneous biaxial stretching device employing the above-mentioned stretching method, a conventionally known stretching method such as a screw method, a pantograph method, or a linear drive method can be employed.
[0071] <Resin layer> Next, the formation of the resin layer constituting the release film in the present invention will be described. The resin layer constituting the release film of the present invention refers to a layer having releasability (release layer). The resin layer is a layer obtained by curing the above-mentioned resin composition of the present invention.
[0072] The resin layer is preferably a coating layer formed by coating a resin composition on a substrate film. Another layer may be provided between the resin layer and the substrate film, but the resin layer may be directly laminated on the substrate film.
[0073] The thickness of the resin layer is preferably 0.05 to 10.0 μm, more preferably 0.06 to 5.0 μm, even more preferably 0.07 to 2.0 μm, even more preferably 0.08 to 1.5 μm, and most preferably 0.09 to 1.0 μm. By making the thickness of the resin layer equal to or greater than the lower limit, a uniform coating film can be formed stably, and sufficient peeling properties and peeling force stability can be easily obtained. In addition, by making the thickness of the resin layer equal to or less than the upper limit, the coating film can be sufficiently cured, and the unreacted components of the resin layer can be prevented from transferring to the adhesive layer, making it easier to achieve low migration. In applications requiring high quality in the coating appearance of the resin layer, such as polarizing plate applications, the thickness of the resin layer is preferably in the range of 0.05 to 2.0 μm, more preferably 0.06 to 1.5 μm, even more preferably 0.07 to 1.0 μm, still more preferably 0.08 to 0.5 μm, and most preferably 0.09 to 0.35 μm. By setting the thickness of the resin layer within the above range, it is possible to obtain a good coating appearance while maintaining sufficient release properties, release force stability, and low migration.
[0074] The amount of the resin composition to be applied when forming the resin layer is preferably 0.05 to 10.0 g / m in terms of solid content. 2 , more preferably 0.06 to 5.0 g / m 2 , and more preferably 0.07 to 2.0 g / m 2 , and more preferably 0.08 to 1.5 g / m 2 , and most preferably 0.09 to 1.0 g / m 2 The range is. When the coating amount of the resin composition is set to the above lower limit or more, a stable and uniform coating film can be formed, and sufficient light peelability and peel strength stability can be easily obtained. Also, when the coating amount of the resin composition is set to the above upper limit or less, the coating film can be sufficiently cured, and the unreacted components of the resin layer can be prevented from transferring to the adhesive layer, making it easy to achieve low migration. In applications where high quality is required for the coating appearance of the resin layer, such as polarizing plate applications, the coating amount of the resin composition when forming the resin layer is preferably 0.05 to 2.0 g / m 2 , more preferably 0.06 to 1.5 g / m 2 , and more preferably 0.07 to 1.0 g / m 2 , and more preferably 0.08 to 0.5 g / m 2 , and most preferably 0.09 to 0.35 g / m 2 By setting the thickness of the resin layer within the above range, it is possible to obtain a good coating appearance while maintaining sufficient release properties, release force stability, and low migration.
[0075] The resin layer may be formed by in-line coating, in which the film surface is treated during the film-forming process of the base film, or by offline coating, in which a coating is applied outside the system onto a base film that has already been produced. More preferably, the resin layer is formed by offline coating.
[0076] The resin layer can be provided on the substrate film by a conventional coating method such as reverse gravure coating, direct gravure coating, roll coating, die coating, bar coating, curtain coating, or the like.
[0077] The substrate film constituting the release film of the present invention may be previously subjected to a surface treatment such as a corona treatment or a plasma treatment.
[0078] The curing conditions for forming the resin layer are not particularly limited. When the resin layer is provided by offline coating, the heat treatment is usually performed at 80°C or higher for 10 seconds or more, preferably at 100 to 200°C for 3 to 40 seconds, more preferably at 120 to 190°C for 3 to 40 seconds, and even more preferably at 150 to 180°C for 3 to 40 seconds.
[0079] If necessary, heat treatment and irradiation with active energy rays such as ultraviolet rays may be used in combination. As an energy source for curing by irradiation with active energy rays, known devices and energy sources can be used. For example, light sources include fusion (H) lamps, metal halide lamps, high-pressure mercury lamps (ozone generating type, ozone-less type), UV-LEDs, etc.
[0080] Although there is no particular limitation on the active energy ray irradiation, in the case of ultraviolet ray irradiation, the active energy ray irradiation condition is 10 to 3000 mJ / cm in terms of the cumulative light amount. 2The range is preferably 50 to 2000 mJ / cm, and more preferably 100 to 1000 mJ / cm. By setting the integrated light amount of ultraviolet irradiation within the above range, the curing of the resin layer is promoted, while by not irradiating excessively, the resin layer is not destroyed and the peeling force after irradiation can be prevented from becoming heavy.
[0081] In the present invention, the coating solution is aged for 8 hours to evaluate the stability of the coating solution. This is to observe the degree to which hydrogen gas is generated by the reaction of the Si-H group of the crosslinking agent with the catalyst in the coating solution. When the Si-H group of the crosslinking agent reacts with the catalyst to generate hydrogen gas and the Si-H group is consumed excessively, there is a shortage of Si-H groups that should be crosslinked, so there is a problem that a heavy peeling phenomenon occurs due to poor curing in the next press process (evaluation of the effect of the winding pressure when the release film is wound on a roll). In the present invention, when it is difficult to achieve the desired curing reaction of the silicone resin simply by controlling the Si-H / alkenyl group ratio, as in the conventional method, the proportion of SiH groups among the substituents bonded to the siloxane moiety in the crosslinking agent is controlled within a specified range, thereby promoting a good curing reaction at the maximum level possible, thereby achieving light peelability.
[0082] The curable silicone resin used in this embodiment may contain a silicone crosslinking agent containing a SiH group. In this case, the amount of alkenyl groups linked to the polysiloxane chain of the curable silicone resin is the amount of alkenyl groups in the curable silicone resin containing the silicone crosslinking agent (crosslinking agent A and crosslinking agent B), and is the amount of alkenyl groups relative to the total amount of siloxane components in the curable silicone resin containing the silicone crosslinking agent.
[0083] The heat peeling force (FA) of the resin layer in the release film of the present invention against the acrylic adhesive layer (No. 502) is preferably 30 mN / cm or less, more preferably 28 mN / cm or less, and even more preferably 26 mN / cm or less. The heat peeling force (FA) is the peeling force after laminating the resin layer and the acrylic adhesive layer (No. 502) in the release film, leaving them at 100°C for 1 hour, and then leaving them at room temperature (23°C) for 1 hour. When the heat peeling force (FA) is set to the above lower limit or more, good peeling properties can be exhibited without deformation or breakage of the adhesive layer even in a heated environment. On the other hand, when the heat peeling force (FA) is set to the above upper limit or less, light peeling properties can be achieved even in a heated environment such as, for example, a manufacturing process having a heat treatment step. When measuring the heat peel strength (FA), an adhesive tape (Nitto Denko "No. 502") is applied to the resin layer side of the release film with a rubber roller (2 kg) (twice back and forth), then cut into a size of 25 mm x 300 mm, left at 100°C for 1 hour, and then left at room temperature for 1 hour, after which the peel strength is measured. The peel strength is measured using Intesco Model 2001 manufactured by Intesco Corporation, with the release film peeled at 180° under the condition of a tensile speed of 0.3 m / min.
[0084] In addition, the heat peeling force (FB) of the resin layer in the release film of the present invention against the acrylic adhesive layer (No. 7475) is preferably 30 mN / cm or less, more preferably 28 mN / cm or less, and even more preferably 26 mN / cm or less. The heat peeling force (FB) is the peeling force after laminating the resin layer and the acrylic adhesive layer (No. 7475) in the release film, leaving them at 100°C for 1 hour, and then leaving them at room temperature (23°C) for 1 hour. When the heat peeling force (FB) is the lower limit or more, good peeling properties can be exhibited without deformation or breakage of the adhesive layer even in a heated environment. On the other hand, when the heat peeling force (FB) is the upper limit or less, light peeling properties can be achieved even in a heated environment such as a manufacturing process having a heat treatment step. When measuring the heat peel strength (FB), an adhesive tape (Tesa's "No. 7475") is pressed (twice back and forth) onto the resin layer side of the release film with a rubber roller (2 kg), then cut into a size of 25 mm x 300 mm, left at 100°C for 1 hour, and then left at room temperature for 1 hour, after which the peel strength is measured. The peel strength is measured using Intesco's "Intesco Model 2001" at a tensile speed of 0.3 m / min, by peeling the release film at 180°.
[0085] <Undercoat layer> The present release film may have an undercoat layer between the substrate film and the resin layer. The undercoat layer is not only used for the purpose of improving the adhesion between the base film and the resin layer, but may also be used for the purpose of imparting various functions to the release film. Examples of the undercoat layer include an antistatic layer for suppressing peeling electrification in the process of peeling off a functional layer such as an adhesive layer provided on a resin layer and preventing adhesion of foreign matter, and an oligomer sealing layer for sealing the precipitation of oligomers from a polyester film when performing heat treatment at high temperature for a long time. The undercoat layer may be a single layer or a structure of two or more layers.
[0086] The undercoat layer (antistatic layer) having antistatic properties preferably contains the following (a) to (c). The component (a) is an antistatic agent, and can be, for example, a polymer in which a compound made of thiophene or a thiophene derivative is doped with another anionic compound, or a self-doped polymer having an anionic group in a compound made of thiophene or a thiophene derivative, or a polymer containing a monomer having an alkylsulfonate ion as a counter ion as a component. These antistatic agents can be used alone or in combination of two or more.
[0087] In forming an undercoat layer having antistatic properties, it is possible to use (b) a polyhydroxy compound which is one or more compounds selected from polyglycerin represented by formula (4) and alkylene oxide adducts of polyglycerin or derivatives thereof, in order to improve the antistatic properties.
[0088] [ka]
[0089] The undercoat layer may contain a binder component as component (c), and may be any of various conventionally known polymers, such as polyurethane resins, polyester resins, acrylic resins, polyvinyl alcohol resins, etc. Among these, it is preferable to use one or more compounds selected from the group consisting of polyurethane resins, polyester resins, and acrylic resins.
[0090] The release film of the present invention has an antistatic undercoat layer, and thus has a surface resistivity of at least one surface of 1×10 12 It is preferably Ω / □ or less. The surface resistivity can be measured in accordance with JIS K-6911-1955.
[0091] In addition, the undercoat layer having oligomer sealing properties (oligomer sealing layer) may be provided with an undercoat layer having oligomer sealing properties that contains an organic compound containing one or more metal elements selected from aluminum, titanium, and zirconium. The undercoat layer having oligomer sealing properties may be provided directly on the substrate film, or may be provided on an undercoat layer having antistatic properties.
[0092] In addition, in order to improve the strength of the undercoat layer, a crosslinking agent can be used in combination. The crosslinking agent can be a conventionally known material, such as an oxazoline compound, an epoxy compound, a melamine compound, an isocyanate compound, a carbodiimide compound, an organic silicon compound, etc. Two or more types of crosslinking agents can be used in combination.
[0093] The undercoat layer may contain unreacted compounds of the various compounds in the resin composition, reacted compounds, or a mixture thereof.
[0094] The thickness of the undercoat layer is not particularly limited, but is preferably 0.005 μm to 0.5 μm, more preferably 0.008 μm to 0.25 μm, and even more preferably 0.01 μm to 0.15 μm. If the thickness of the undercoat layer is within the above range, good functionality (e.g., antistatic performance and oligomer sealing performance) can be imparted to the release film.
[0095] The undercoat layer is formed by coating a coating liquid onto a film, and may be formed by in-line coating carried out during the film production process, or may be formed by applying the coating outside the system onto a film that has already been produced, so-called off-line coating, with in-line coating being more preferred.
[0096] In-line coating is a method of coating within the polyester film production process, specifically, a method of coating at any stage from melt extrusion of polyester to stretching, heat setting and winding up. Usually, coating is performed on any of the following: an unstretched sheet obtained by melting and quenching, a stretched uniaxially stretched film, a biaxially stretched film before heat setting, or a film after heat setting and before winding up. Although not limited to the following, for example, in the case of sequential biaxial stretching, a method in which a uniaxially stretched film stretched in the longitudinal direction (machine direction) is coated and then stretched in the transverse direction is particularly excellent. This method has the advantage of being able to simultaneously form the film and the undercoat layer, and is advantageous in terms of production costs. In addition, since stretching is performed after coating, the thickness of the undercoat layer can be changed by the stretching ratio, and thin film coating can be performed more easily than with off-line coating films. In addition, by providing an undercoat layer on the film before stretching, the undercoat layer can be stretched together with the polyester film, and thus the undercoat layer can be firmly attached to the polyester film. Furthermore, in the production of biaxially stretched polyester film, by stretching while holding the film ends with clips or the like, the film can be restrained in the longitudinal and lateral directions, and in the heat setting step, high temperatures can be applied while maintaining flatness and without wrinkles, etc. Therefore, the heat treatment performed after coating can be at a high temperature that cannot be achieved by other methods, and the undercoat layer hardens more rapidly than in offline coating, making it possible to create a stronger coating film.
[0097] When the undercoat layer is provided by in-line coating, it is preferable to produce the base film by coating the polyester film with an undercoat layer composition prepared by preparing an aqueous solution or aqueous dispersion of the above-mentioned series of compounds so that the solids concentration (total non-volatile components) is adjusted to approximately 0.1 to 50 mass %.
[0098] The drying and curing conditions when forming an undercoat layer on a substrate film are not particularly limited. When the undercoat layer is formed by in-line coating, the heat treatment is preferably performed at 70 to 270°C for 3 to 200 seconds, more preferably at 100 to 260°C, and even more preferably at 110 to 250°C for 10 to 100 seconds.
[0099] Regardless of whether off-line coating or in-line coating is used, heat treatment and irradiation with active energy rays such as ultraviolet rays may be used in combination, if necessary.
[0100] <Release film with adhesive layer> This embodiment may be a release film with an adhesive layer, which is provided on the resin layer of the release film described above. It is particularly preferable that the adhesive layer is an acrylic adhesive layer. In the release film described above, both light peelability and peel stability are achieved, and furthermore, the silicone non-migration property is extremely excellent, so that even when an adhesive layer is laminated on a resin layer, the silicone contained in the resin layer is suppressed from migrating to the adhesive layer. For this reason, it is particularly preferable that the release film with an adhesive layer is used during semiconductor manufacturing.
[0101] Examples of the adhesive constituting the adhesive layer include various known polymers such as acrylic, rubber, polyester, urethane, polyether, silicone, polyamide, fluorine, etc. Among them, the adhesive is preferably an acrylic polymer, and the adhesive composition is preferably an emulsion type composition in which an acrylic polymer is dispersed in water (water-dispersed acrylic adhesive composition) or a composition in which an acrylic polymer is dissolved in ethyl acetate (ethyl acetate solvent-type acrylic adhesive composition).
[0102] The adhesive constituting the adhesive layer is preferably an acrylic adhesive using poly(meth)acrylic acid ester or a copolymer of (meth)acrylic acid ester and other monomers (hereinafter collectively referred to as acrylic polymer). In the present invention, the term "(meth)acrylic acid ester" means either or both of "acrylic" and "methacrylic".
[0103] Examples of the (meth)acrylic acid ester include methyl (meth)acrylate, ethyl (meth)acrylate, propyl (meth)acrylate, isopropyl (meth)acrylate, butyl (meth)acrylate, isobutyl (meth)acrylate, s-butyl (meth)acrylate, t-butyl (meth)acrylate, pentyl (meth)acrylate, hexyl (meth)acrylate, heptyl (meth)acrylate, octyl (meth)acrylate, isooctyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, nonyl (meth)acrylate, isononyl (meth)acrylate, decyl (meth)acrylate, isodecyl (meth)acrylate, undecyl (meth)acrylate, dodecyl (meth)acrylate, tridecyl (meth)acrylate, tetradecyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, 2-methylpropyl ... Examples of the (meth)acrylic acid esters include pentadecyl acrylate, hexadecyl (meth)acrylate, heptadecyl (meth)acrylate, octadecyl (meth)acrylate, etc.; cycloalkyl (meth)acrylic acid esters such as cyclohexyl (meth)acrylate, etc.; aryl (meth)acrylic acid esters such as phenyl (meth)acrylate, etc. The (meth)acrylic acid esters can be used alone or in combination of two or more kinds.
[0104] In addition, when the acrylic adhesive is an ultraviolet-curable acrylic adhesive, an ultraviolet-curable carbon-carbon double bond may be introduced into the acrylic polymer. In this case, the constituent components of the acrylic polymer may be copolymerized with a monomer having a functional group to prepare an acrylic polymer having a functional group, and then the functional group in the acrylic polymer having a functional group may be reacted with a compound having a carbon-carbon double bond to introduce the ultraviolet-curable carbon-carbon double bond into the acrylic polymer.
[0105] The acrylic polymer having a functional group can be obtained by copolymerizing a monomer (copolymerizable monomer) that is copolymerizable with the (meth)acrylic acid ester as a constituent and has a functional group such as a hydroxyl group, a carboxyl group, or a glycidyl group. Examples of the monomer that is copolymerizable with the (meth)acrylic acid ester and has a hydroxyl group include 2-hydroxyethyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, 4-hydroxybutyl (meth)acrylate, 6-hydroxyhexyl (meth)acrylate, polyethylene glycol mono(meth)acrylate, polypropylene glycol mono(meth)acrylate, and glycerin mono(meth)acrylate. Examples of the monomer that is copolymerizable with the (meth)acrylic acid ester and has a carboxyl group include (meth)acrylic acid (acrylic acid, methacrylic acid), itaconic acid, maleic acid, fumaric acid, crotonic acid, and isocrotonic acid. Examples of the monomer that is copolymerizable with the (meth)acrylic acid ester and has a glycidyl group include glycidyl (meth)acrylate.
[0106] From the viewpoint of preventing contamination of workpieces such as wafers used in semiconductor devices, the acrylic polymer preferably has a low content of low molecular weight substances, and the weight average molecular weight is preferably 100,000 or more, more preferably 200,000 or more. On the other hand, from the viewpoint of handling, the upper limit is preferably 2,000,000 or less.
[0107] From the viewpoint of exhibiting adhesive properties, the acrylic polymer preferably has a glass transition point in the range of −70° C. to 0° C., and more preferably in the range of −65° C. to −20° C. By satisfying the above range, it is possible to achieve both the formation of a stable adhesive layer coating film and the ensuring of wettability to the adherend.
[0108] The thickness of the adhesive layer is preferably from 5 μm to 80 μm, more preferably from 8 μm to 60 μm, and particularly preferably from 10 μm to 40 μm.
[0109] <Method of forming adhesive layer> The method for forming the adhesive layer is not particularly limited, and the adhesive layer may be formed by applying the above-mentioned adhesive composition onto the resin layer of the present release film, followed by appropriate drying, curing, etc. Alternatively, the adhesive layer may be formed by applying the above-mentioned adhesive composition onto a base film or a release film having a release strength different from that of the present release film, followed by appropriate drying, curing, etc., and then laminating the release layer (resin layer) of the present release film to the surface opposite to the surface provided with the release film having a release strength different from that of the present release film. The pressure-sensitive adhesive composition may be cured depending on the crosslinking agent and main component resin, and may be cured by heating or by irradiation with light such as ultraviolet light. The pressure-sensitive adhesive composition may be appropriately diluted with an organic solvent or the like and then applied onto a release layer or the like.
[0110] <Adhesive sheet> The adhesive sheet of the present invention comprises the above-mentioned release film and another release film via an adhesive layer. That is, the adhesive sheet comprises another release film via the adhesive layer of the above-mentioned release film with adhesive layer. As described above, the adhesive layer is preferably formed from an acrylic adhesive layer composition. In addition, it is particularly preferably an optical transparent adhesive sheet. The other release film is not particularly limited, and may be any resin film having releasability.
[0111] <How to use the adhesive sheet> The pressure-sensitive adhesive sheet of the present invention can be used by peeling off the other release film and then attaching the exposed pressure-sensitive adhesive layer surface to an optical member. The pressure-sensitive adhesive sheet of the present invention can be used in various laminated configurations. For example, the release film with the pressure-sensitive adhesive layer may be a film laminate in which an optical member is attached to the surface of the pressure-sensitive adhesive layer. Such a film laminate can be produced by peeling off the release film and attaching the optical member to the adherend by the exposed pressure-sensitive adhesive layer. Examples of the optical member include a polarizing plate and a touch sensor. The optical member may also be an in-vehicle optical member such as a touch panel mounted on an automobile.
[0112] (Polarizing plate) The material and structure of the polarizing plate are arbitrary, and for example, a polarizing plate of this type is widely used in which a TAC (triacetyl cellulose) film is laminated as a protective film on a stretched polyvinyl alcohol film using iodine as an orientation dye. The polarizing plate may have a layer structure on the surface that has a hard coat having substantially no phase difference, anti-glare, low reflection, anti-static, etc.
[0113] (Touch Sensor) A touch sensor is a component that detects the touched point when a user touches an image displayed on a screen with a finger or a touch pen. Depending on the sensor technology, examples include a capacitive type, a resistive film type, and a surface wave type using infrared rays or ultrasound. Touch sensors are generally installed in display devices such as liquid crystal display panels and organic electroluminescence (EL) displays. In recent years, there has been a trend to use a base film as an alternative to a glass substrate, focusing on flexibility, and it is preferable to use a touch sensor film. The touch sensor film generally has a patterned transparent conductive layer for performing the function of a sensing electrode.
[0114] <<<Explanation of terms, etc.>>> In the present invention, the term "film" includes the term "sheet", and the term "sheet" includes the term "film". Furthermore, when the term "panel" is used, such as an image display panel, a protective panel, a touch panel, etc., it encompasses a plate, a sheet, and a film.
[0115] In the present invention, when it is described as "X to Y" (X and Y are any numbers), unless otherwise specified, it includes the meaning of "X or more and Y or less", as well as the meaning of "preferably larger than X" or "preferably smaller than Y". In addition, when it is stated that the amount is "X or more" (X is any number), it also means that the amount is "preferably greater than X" unless otherwise specified, and when it is stated that the amount is "Y or less" (Y is any number), it also means that the amount is "preferably smaller than Y" unless otherwise specified. EXAMPLES
[0116] The present invention will be described in more detail below with reference to examples, but the present invention is not limited to the following examples as long as it does not deviate from the gist of the invention. The evaluation methods in the examples and comparative examples are as follows.
[0117] (1) Method for measuring intrinsic viscosity of polyester 1 g of polyester from which other polymer components incompatible with polyester and pigments had been removed was precisely weighed and dissolved in 100 ml of a mixed solvent of phenol / tetrachloroethane = 50 / 50 (mass ratio), and the intrinsic viscosity was measured at 30°C.
[0118] (2) Measurement method for average particle size (d50: μm) The cumulative 50% (mass basis) value in the equivalent sphericity distribution measured using a centrifugal sedimentation type particle size distribution measuring device (SA-CP3 type manufactured by Shimadzu Corporation) was taken as the average particle size.
[0119] (3) Molecular weight measurement of curable silicone resin The chromatogram was measured using a GPC measuring device, and the number average molecular weight (Mn) and mass average molecular weight (Mw) were obtained based on a calibration curve using standard polystyrene. When the curable silicone resin contained a silicone crosslinker, the mass average molecular weight (Mn) and number average molecular weight (Mw) were obtained excluding the peak derived from the silicone crosslinker. Specifically, 4 mg of the sample for measurement was dissolved in 4 mL of THF to prepare a measurement solution, and 100 μL of the measurement solution was injected into the GPC measuring device for measurement. Tetrahydrofuran (THF) was used as the eluent. For the analysis, Tosoh Corporation's "Ecosec8320" was used, Tosoh Corporation's "TSKgel guardcolumn HXL-L" was used as the guard column, and four Tosoh Corporation's "TSKgel GMHXL" were used as the column in connection. In addition, the analysis was performed under the conditions of an oven temperature of 40°C and a THF flow rate of 1.0 mL / min, and RI was used for detection.
[0120] (4) Composition analysis of curable silicone resin The composition of the curable silicone resins used in the examples and comparative examples was analyzed using a 400 MHz-NMR (Bruker Avance400M). 1 H-NMR measurements were performed at 30° C. using CDCl3 as a solvent and the peak derived from the methyl group of dimethylsiloxane as the chemical shift standard. The contents (mol%) of alkenyl groups (Vi) and SiH groups relative to the total amount of siloxane components in the polysiloxane chain were evaluated from the integral ratio of each functional group when the methyl group (SiCH3) was used as the standard.
[0121] (5) Measurement of thermal peel strength (FA) of resin layer An adhesive tape (Nitto Denko "No. 502") was applied to the resin layer side of the release film with a rubber roller (2 kg) (twice back and forth), then cut to a size of 25 mm x 300 mm and left at 100°C for 1 hour. After leaving it at room temperature for 1 hour, the peel strength was measured. The peel strength was measured using Intesco Model 2001 manufactured by Intesco Corporation, and the release film was peeled at 180° under the condition of a tensile speed of 0.3 m / min.
[0122] (6) Measurement of thermal peel strength (FB) of resin layer An adhesive tape (Tesa's "No. 7475") was applied to the resin layer side of the release film with a rubber roller (2 kg) (twice back and forth), then cut to a size of 25 mm x 300 mm and left at 100°C for 1 hour. The tape was then left at room temperature for 1 hour, after which the peel strength was measured. The peel strength was measured using Intesco's "Intesco Model 2001" at a tensile speed of 0.3 m / min, with the release film peeled at 180°.
[0123] The polyesters used in the base films of the Examples and Comparative Examples were prepared as follows.
[0124] <Materials used> Raw material A (polyester (A)): Dicarboxylic acid component (a-1): terephthalic acid = 100 mol %, diol component (a-2): ethylene glycol = 100 mol %; homopolyethylene terephthalate (intrinsic viscosity = 0.59 dL / g) Raw material B (polyester (B)): Masterbatch containing homopolyethylene terephthalate and 1.0% by mass of silica particles with an average particle size of 3.5 μm (intrinsic viscosity = 0.70 dL / g)
[0125] <Materials used in the undercoat layer> (Compound (a)) (AI): Conductive agent consisting of polyethylenedioxythiophene and polystyrenesulfonic acid (Orgacon ICP1010 manufactured by Agfa-Gevaert) neutralized with concentrated ammonia water to pH=9; non-volatile component: 1.2% by mass; solvent: water
[0126] (Compound (c)) (CII): A compound in which an average of four molecules of polyethylene oxide are added to a polyglycerin skeleton in the above formula (3), where the average n=4.
[0127] (Antistatic agent) (DI): Antistatic agent (quaternary ammonium salt compound), poly(trimethylammonium ethyl methacrylate methanesulfonate), number average molecular weight 30,000
[0128] (binder) (EI): Polyvinyl alcohol with a saponification degree of 88 mol% and a polymerization degree of 500 (EII): Aqueous dispersion of urethane resin polymerized with the following composition When polyester polyol (C1a) is composed of 282 parts by mass of terephthalic acid, 282 parts by mass of isophthalic acid, 62 parts by mass of ethylene glycol, and 250 parts by mass of neopentyl glycol, a polyester polyurethane composed of 876 parts by mass of (C1a), 244 parts by mass of tolylene diisocyanate, 81 parts by mass of ethylene glycol, and 67 parts by mass of dimethylolpropionic acid was neutralized with ammonia and dispersed in water (concentration 20%, viscosity at 25°C 50 mPa s)
[0129] (Crosslinking agent) (FI): Hexamethoxymethylolmelamine
[0130] (Surfactant) (GI): A nonionic surfactant having a structure having polyethylene oxide in the side chain, as shown in the following formula:
[0131] [ka] Undercoat layer composition 1: DI / EI / FI=40 / 20 / 40 (mass%) Undercoat layer composition 2: AI / CII / EII / GI=10 / 30 / 55 / 5 (mass%)
[0132] Manufacturing Example 1: Base Film 1 The mixed raw material obtained by mixing polyesters (A) and (B) at a ratio of 90% by mass and 10% by mass, respectively, was used as the raw material for the outermost layer (surface layer), and polyester (A) was used as the raw material for the intermediate layer. Each was fed to two extruders and melted at 290°C. Then, on a cooling roll set at 25°C, a layer structure of two kinds and three layers (extrusion amount of surface layer / intermediate layer / surface layer = 1:8:1) was coextruded and cooled and solidified to obtain an unstretched sheet. Next, the film was stretched 3.4 times in the longitudinal direction at a film temperature of 85°C using the roll peripheral speed difference, and then the undercoat layer composition 1 was applied, and the film was introduced into a tenter and stretched 4.7 times in the transverse direction at 120°C. After heat treatment at 225°C, the film was relaxed by 2% in the transverse direction to obtain a biaxially stretched polyester film (substrate film 1) having a thickness of 38 μm.
[0133] Manufacturing Example 2: Base Film 2 The mixed raw material obtained by mixing polyesters (A) and (B) at a ratio of 90% by mass and 10% by mass, respectively, was used as the raw material for the outermost layer (surface layer), and polyester (A) was used as the raw material for the intermediate layer, and each was fed to two extruders and melted at 290°C. Thereafter, the layer structure of two types and three layers (surface layer / intermediate layer / surface layer=1:8:1 discharge amount) was coextruded onto a cooling roll set at 25°C, cooled and solidified to obtain an unstretched sheet. Next, the film was stretched 3.4 times in the longitudinal direction at a film temperature of 85°C using the roll peripheral speed difference, and then the undercoat layer composition 2 was applied to both sides, and then the film was introduced into a tenter and stretched 4.7 times in the transverse direction at 120°C. After heat treatment at 225°C, the film was relaxed by 2% in the transverse direction to obtain a biaxially stretched polyester film (substrate film 2) having a thickness of 50 μm.
[0134] Examples of the compounds constituting the resin composition are as follows. a1: Curable silicone resin (a silicone resin in which a vinyl group (represented as Vi in the table) has been introduced into the side chain and / or end of the main chain containing a siloxane bond, number average molecular weight: 10600, amount of alkenyl groups relative to the total amount of siloxane components in the polysiloxane chain: 1.0 mol%, and a branched structure in the main chain containing a siloxane bond)
[0135] b1: Silicone crosslinking agent (of the substituents bonded to the siloxane moiety, the proportion of SiH groups is 34.1 mol%) b2: Silicone crosslinker (SiH groups account for 30.5 mol% of the substituents bonded to the siloxane moiety) b3: Silicone crosslinker (SiH groups account for 45.4 mol% of the substituents bonded to the siloxane moiety) c1: Addition type platinum catalyst (CM678: Momentive) The compositions of the curable silicone resin, crosslinker A, and crosslinker B are shown in Table 1.
[0136] [Table 1]
[0137] Example 1 Resin composition 2 shown in Table 2 was diluted with a mixed solvent of MEK / n-heptane = 1 / 10 (mass ratio). The diluted resin composition 2 was applied to the surface of the undercoat layer of a polyester film (substrate film 1) by a bar coating method using a No. 4 bar so that the coating thickness (after drying) was 0.12 μm, and then dried at 150 ° C. for 15 seconds to obtain a release film.
[0138] Examples 2 to 11 A release film was obtained by producing in the same manner as in Example 1, except that resin composition 2 was changed to the resin composition, solid content concentration, base film, and aging time described in Table 2, and the coating liquid was aged for a specified time and then applied to the base film.
[0139] Comparative Examples 1 to 5 A release film was obtained by producing in the same manner as in Example 1, except that resin composition 2 was changed to the resin composition, base film, and aging time shown in Table 2, and the coating liquid was aged for a specified time and then applied to the base film.
[0140] [Table 2]
[0141] As shown in Table 2, the release films obtained in the examples all showed a light heat peel strength compared to the conventional technology (using crosslinking agent b3 alone), and were not prone to heavy peel strength even after heat treatment.
[0142] This tendency was particularly pronounced when the aging time of the coating liquid was short (for example, from a comparison between Examples 1 and 2 and Comparative Example 1, or a comparison between Examples 3 and 4 and Comparative Example 2). In addition, when the coating liquid is aged for 8 hours, if the amount of SiH groups is too small, it usually induces poor curing and tends to become easily peeled off after the next press treatment. In the present invention, it has been found that by controlling the ratio of SiH groups among the substituents bonded to the siloxane part in the crosslinking agent to a predetermined range, it is possible to maintain the pot life of the coating liquid while preventing heavy peeling. It is presumed that the curing of the surface part proceeds smoothly during the resin layer formation process due to the effect of improving the dispersibility of the crosslinking agent in the coating liquid. [Industrial Applicability]
[0143] The release film of the present invention can provide a silicone release film that realizes light release properties and is not easily changed by pressing, and has high industrial value.In particular, it is suitable for applications that do not want to change the release properties of the release layer and the appearance of the resin layer surface to deteriorate, and can be used for various applications such as capacitive touch panel manufacturing, bonding via an adhesive layer, optical members (polarizing plate, retardation plate, prism sheet, conductive film, resin film, glass substrate, etc.) used in LCD, organic EL component manufacturing, and various display component manufacturing such as LCD, as well as various adhesive layer protection applications. [Explanation of symbols]
[0144] 10. Base film 20 Resin layer 100 Release film
Claims
1. A resin composition comprising a curable silicone resin, a crosslinking agent A, and a catalyst, wherein the crosslinking agent A is a silicone crosslinking agent, and the proportion of SiH groups among substituents bonded to siloxane moieties is 25 mol % or more and 42 mol % or less.
2. 2. The resin composition according to claim 1, further comprising a crosslinking agent B having a higher proportion of SiH groups among the substituents bonded to the siloxane moieties than crosslinking agent A.
3. The resin composition according to claim 2 , wherein a ratio of SiH groups to the substituents bonded to the siloxane moieties of the crosslinking agent B is 30 mol % or more and 50 mol % or less.
4. 3. The resin composition according to claim 1, wherein the curable silicone resin contains two or more crosslinkable reactive groups and has a number average molecular weight of 3,000 to 250,000.
5. The resin composition according to claim 1 or 2, wherein the curable silicone resin has a branched structure in a main chain containing a siloxane bond.
6. The resin composition according to claim 1 or 2, which is diluted with a solvent.
7. A release film comprising a base film and a resin layer on at least one surface thereof, the resin layer being a cured product of the resin composition according to claim 1 or 2.
8. The release film according to claim 7 , further comprising an undercoat layer between the base film and the resin layer.
9. The release film according to claim 8 , wherein the undercoat layer is an antistatic layer.
10. The release film according to claim 9, wherein the undercoat layer contains the following compounds (a) to (c): (a) at least one selected from a polymer in which a compound made of thiophene or a thiophene derivative is doped with another anionic compound, a self-doped polymer having an anionic group in a compound made of thiophene or a thiophene derivative, and a polymer containing, as a component, a monomer having an alkylsulfonate ion as a counter ion; (b) Polyhydroxy Compound (c) one or more compounds selected from the group consisting of polyurethane resins, polyester resins, and acrylic resins
11. At least one surface has a surface resistivity of 1×10 12 The release film according to claim 9, having a resistance to deformation of Ω / □ or less.
12. 9. The release film of claim 8, wherein the undercoat layer is an oligomeric sealing layer.
13. The release film according to claim 7 , wherein the base film is a polyester film.
14. The release film according to claim 13 , wherein the polyester film has a three-layer structure.
15. A pressure-sensitive adhesive sheet comprising the release film according to claim 7 and another release film via a pressure-sensitive adhesive layer.
16. The adhesive sheet according to claim 15 , wherein the adhesive layer is formed from an acrylic adhesive layer composition.
17. The pressure-sensitive adhesive sheet according to claim 15, which is for use as an optically transparent pressure-sensitive adhesive sheet.
18. A method for using the pressure-sensitive adhesive sheet according to claim 16, comprising peeling off the other release film and then attaching the exposed surface of the pressure-sensitive adhesive layer to an optical member.
19. The method for using the pressure-sensitive adhesive sheet according to claim 18, wherein the optical component is a polarizing plate or a touch sensor.
Citation Information
Patent Citations
Release film
JP2004255704A
Mold release film excellent in releaseability
JP2016165825A
Release film with excellent releasability
JP2017061081A